2021
DOI: 10.1093/mnras/stab2283
|View full text |Cite
|
Sign up to set email alerts
|

NuSTAR observations of a repeatedly microflaring active region

Abstract: We investigate the spatial, temporal, and spectral properties of 10 microflares from AR12721 on 2018 September 9 and 10 observed in X-rays using the Nuclear Spectroscopic Telescope ARray and the Solar Dynamic Observatory’s Atmospheric Imaging Assembly and Helioseismic and Magnetic Imager. We find GOES sub-A class equivalent microflare energies of 1026–1028 erg reaching temperatures up to 10 MK with consistent quiescent or hot active region (AR) core plasma temperatures of 3–4 MK. One microflare (SOL2018-09-09T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 60 publications
(85 reference statements)
3
14
0
Order By: Relevance
“…As a result, the SDO/AIA 211 Å lightcurves for these features sometimes do not show behaviour consistent with Hinode/XRT or with NuSTAR. Previous analysis of microflares observed with NuSTAR (for example, Cooper et al (2020Cooper et al ( , 2021) has made use of the SDO/AIA Fe XVIII proxy channel (Del Zanna, 2013). Unfortunately, the temperatures of these quiet Sun features are too low for this to be useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the SDO/AIA 211 Å lightcurves for these features sometimes do not show behaviour consistent with Hinode/XRT or with NuSTAR. Previous analysis of microflares observed with NuSTAR (for example, Cooper et al (2020Cooper et al ( , 2021) has made use of the SDO/AIA Fe XVIII proxy channel (Del Zanna, 2013). Unfortunately, the temperatures of these quiet Sun features are too low for this to be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2014, there have been a number of NuSTAR solar observing campaigns 1 . Much of the work on the NuSTAR solar observations has focused on active region microflares (Wright et al, 2017;Glesener et al, 2017;Hannah et al, 2019;Cooper et al, 2020;Duncan et al, 2021;Cooper et al, 2021), with Glesener et al (2020) reporting for the first time on non-thermal emission detected in a microflare observed with NuSTAR. Kuhar et al (2017) presented work on quiet Sun flares observed by NuSTAR outside of an active region, finding that their temperatures ranged from 3.2-4.1 MK.…”
Section: Introductionmentioning
confidence: 99%
“…A large spectral index (δ = 7) was chosen for the energy distribution, supported by observational evidence of increasing spectral index with decreasing flare energy (Hannah et al 2011), and compatible with values from rare hard X-ray observations of these small heating events (e.g., Glesener et al 2020;Cooper et al 2021). The low-energy cutoff values E C = 5, 10, and 15 keV were chosen to represent beams that are dominated by low-, intermediate-, and high-energy electrons.…”
Section: Parameter Surveymentioning
confidence: 99%
“…Signatures of non-thermal electrons are found in spectra from hard X-ray observations of active region flares. However, X-ray observations of small-scale events with energies in the range 10 24 -10 25 erg remain rare because signatures from non-thermal electrons are typically below the detection threshold (although, see e.g., Wright et al 2017;Glesener et al 2020;Cooper et al 2021). Indications of energetic events are obtained in regions that are responsive to heating.…”
Section: Introductionmentioning
confidence: 99%
“…M1-10. Sub-A class (Glesener et al, 2017;Cooper et al, 2021) flares have been observed, as have flares > X10 (e.g., Emslie et al, 2012).…”
Section: Introductionmentioning
confidence: 99%